The characteristics of neonatal sepsis in Low Birth Weight (LBW) infants at Sanglah General Hospital, Bali, Indonesia - Novita Purnamasari Assa; I Wayan Dharma Artana; I Made Kardana; Putu Junara Putra; Made Sukmawati (Intisari Sains Medis, 2020)
Backgrounds: Neonatal sepsis is a significant cause of mortality and long-term morbidity. The preterm infant has high-risk sepsis and its sequelae. Low birth weight infants were more susceptible to sepsis. Initial infections in neonates may not be identified due to non-specific symptoms and sign with the limited laboratory criteria. This study aims to describe the characteristics of neonatal sepsis in low birth weight infants in the neonatology intensive care unit of Sanglah Hospital.Methods: A retrospective cross-sectional study was conducted among 168 infants aged zero to 28 days with birth weights <2,500 grams from May 2017 â€“ April 2018 at Sanglah General Hospital, Bali, Indonesia using a purposive sampling technique. The inclusion criteria were sepsis infants who were hospitalized in neonatology care rooms during the study period at Sanglah General Hospital. Variables assessed in this study were sex, location and mode of delivery, birth weight, gestational age, number of parity, length of stay, the onset of sepsis, as well as the outcome. Data were analysed using SPSS version 17 for Windows.Results: The mortality rate of sepsis in low birth weight infants was 29.8%. Most of the subjects were male (53%), location of delivery at Sanglah Hospital (60.7%), born spontaneously (51.2%), birth weight were 1500-2499 grams (58,3%) and the most gestational ages were 32-36 weeks (44,6%). Early-onset neonatal sepsis (EONS) dominates patients with neonatal sepsis, with a mean length of stay was 23.27Â±20.32 days. The major infection risk factor was premature rupture membrane (PRM) >24 hours (14.9%), and minor infection risk factor was gestational age <37 weeks (78%), very low birth weight (44.6%) and asphyxia (41.1%). The total blood culture positivity was 38 (22.6%) cases, and Enterococcus faecalis was the most common organism in this study.Conclusion: The incidence and mortality of neonatal sepsis in LBW infants were still high. The importance of knowledge and awareness of pregnant women about danger signs and the risk of infection can reduce the incidence of early-onset neonatal sepsis. Prevention of healthcare-associated infections can reduce the incidence of late-onset neonatal sepsis.